A prisão disciplinar por pronta intervenção e manutenção da disciplina à luz da constituição federal - Siglinski, Stefan Hanatzki (2018)
The present dissertation analyzes the applied disciplinary prison as a prompt intervention for the preservation of the discipline, provided for in the Army Disciplinary Regulation, against the fundamental rights and guarantees guaranteed by the current Federal Constitution. The research aims to demonstrate that this modality of disciplinary administrative arrest is not in line with the current legal -constitutional order, consisting of an affront to constitutional principles and guarantees. In the course of the research, it is pointed out that the purpose of this type of imprisonment is to provide an effective tool for military authorities to co nsecrate their power and authority to those subordinate to them, as well as to discourage possible actions of indiscipline by those individuals who do not identify with the military culture, which do not conform to the institutionalized disciplinarization and the strategies of organizational socialization adopted by the Institution. The present study refers to the basic research, which has as its operational logic the deductive method and the qualitative approach. Regarding the method of procedure, the methodology was characterized as bibliographical, with the analysis of legislation, doctrine and jurisprudence. After constitutional analysis of the way in which disciplinary detention is applied for prompt intervention and maintenance of the discipline, it is verified that this modality of disciplinary administrative arrest offends the principles and constitutional guarantees.